Pamięć o Rosji w prozie Vladimira Nabokova - Piotrkowicz, Sylwia (Przegląd Rusycystyczny, 2007)
RUSSIA REMEMBERED IN THE PROSE OF VLADIMIR NABOKOV Summary The purpose of the article is to examine different ways of presenting the topic of Russia in Vladimir Nabokov’s prose. The article presents Nabokov’s Russian works where Russia is the main topic: Mary, The Defense, Glory, The Gift. The characters are the Russians transferred from the pre-revolutionery epoch. The Russian nature, manners, habits, culture have been captured here by the novelist. Several of the Nabokov’s novels can be treated as the autobiographical ones due to their structure or subject. These novels differ in terms of structure as few of them have more concise structure than the others. At the same time all of them are fi lled with the Russian cordiality and friendliness ПАМЯТЬ О РОССИИ В ПРОЗЕ ВЛАДИМИРА НАБОКОВА Резюме Целью настоящей статьи является анализ способа представления темы России, к которой многократно обращался в своем творчестве Владимир Набоков. В статье анализируются русскоязычные произведения автора, в которых доминирует русская тема: Машенька, Защита Лужина, Подвиг, Дар. Выступают здесь русские персонажи, перенесенные в иную обстановку из дореволюционной эпохи, русские нравы, привычки, манеры, русская духовная культура. „Русскость” этой группы произведений вырисовывается в некоторых общих особенностях художественного колорита. Некоторые романы могут быть в структурно жанровом отношении преимущественно автобиографическими. Очередные произведения отличаются друг от друга своей структурой, но в эмоциональном отношении все они погружены в атмосферу русской душевности, домовитости, своего рода общинной доброжелательности.